2016
DOI: 10.1097/wnf.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Eyelid Nystagmus

Abstract: Carbamazepine and derivatives may induce eyelid nystagmus in the setting of acute intoxication. To the best of our knowledge, these are the first cases of drug-related eyelid nystagmus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…& gaze-evoked nystagmus, saccade abnormalities (slowing, inaccuracy, prolonged latency), smooth pursuit impairment, total ophthalmoplegia, oculogyric crisis and eyelid nystagmus [2,[4][5][6][7][8]. The peculiarity of our patient is that this is the first paediatric case to be reported, yet combination therapy is widely used in infants and children with drug-resistant epilepsies.…”
Section: Bm3-bm4 Bm9-bm10 Bm13-bm14 Bm15-bm16 0v-0v Ls1-ls2 Ls4-ls5 L...mentioning
confidence: 77%
“…& gaze-evoked nystagmus, saccade abnormalities (slowing, inaccuracy, prolonged latency), smooth pursuit impairment, total ophthalmoplegia, oculogyric crisis and eyelid nystagmus [2,[4][5][6][7][8]. The peculiarity of our patient is that this is the first paediatric case to be reported, yet combination therapy is widely used in infants and children with drug-resistant epilepsies.…”
Section: Bm3-bm4 Bm9-bm10 Bm13-bm14 Bm15-bm16 0v-0v Ls1-ls2 Ls4-ls5 L...mentioning
confidence: 77%
“…Eyelid nystagmus was first recognized in 1916 by Pick 1 . Very few other cases have been reported, whose features are summed in Table 1 1–13 . Although the phenomenology shows resemblances in all cases, there are differential features that raise pathophysiological questions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Very few other cases have been reported, whose features are summed in Table 1. [1][2][3][4][5][6][7][8][9][10][11][12][13] Although the phenomenology shows resemblances in all cases, there are differential features that raise pathophysiological questions. Some cases are coupled with the fast phase of ocular vertical nystagmus, which may point to an aberrant activation of the otherwise normally coordinated movement of the lids and eyes, reported in lesions possibly involving the ventral tegmental tract.…”
Section: Discussionmentioning
confidence: 99%
“…Eyelid nystagmus has been associated with numerous pathological conditions, including midbrain tumors, pontine or mesencephalic hemorrhage, Wallenberg syndrome, pontomesencephalic stroke, cerebellar tumor and trauma, brainstem angioma, Miller-Fisher syndrome, and chronic alcohol abuse. Eyelid nystagmus was also described as a sign of drug intoxication (3).…”
mentioning
confidence: 99%
“…The authors hypothesized that the abnormal lid movements somehow resulted from an abnormal innervational milieu created by the dorsal midbrain lesion involving cell bodies of neurons that bilaterally innervate the levator muscle in the central caudal nucleus (1). Matarazzo et al (3) presented 2 cases of ocular nystagmus and eyelid nystagmus in primary position exacerbated in the lateral gaze, induced by carbamazepine and oxcarbazepine intoxication. They suggested that impairment of pretectal pathways may be the cause.…”
mentioning
confidence: 99%